Contribution of the major HCHO metabolic pathways to HCHO-uptake by geranium leaves under liquid HCHO stress - Han Shuang; Xiao Suqin; Sun Zhen; Xuan Xiuxia; Li Kunzhi; Chen Limei (浙江大学学报. 农业与生命科学版, 2015)
Geranium (Pelargonium sp. Frensham) is an ornamental plant cultivated in the worldwide. In this study, wild type (WT) geranium leaves were first treated with H13CHO solutions in time and concentration-gradient manner to clarify the detailed H13CHO-metabolic pathways in WT geranium leaves and to quantitatively analyze the roles of the major HCHO-metabolic pathways in HCHO-absorption by WT geranium leaves, and then understand the metabolic mechanism of geranium response to liquid HCHO stress.Geranium was used as the experimental material. In the H13CHO treatment, 2 g geranium fresh leaves were soaked in different concentrations of H13CHO [including 0.1% 2-(N-morpholino) ethanesulfonic acid, MES] solution (100 mL), and then incubated under constant light [100 μmol/(m2·s)] at 25℃ for different time with shaking (100 r/min). After incubation, the leaves were washed and used to grind. The extract was transferred into a 5 mm NMR tube and subjected to 13C-NMR analysis. Resonance peaks were assigned by comparison with authentic compound's chemical shifts and confirmed by spiking the kalium phosphate buffer (KPB) extracts with authentic reference standards. For comparison of the relative contents of the metabolites, the target peaks were integrated relatively to the reference. Geranium leaves were treated in H13CHO solution to analyze the detailed HCHO metabolic pathways and the contribution of the major metabolic pathway to HCHO-uptake by geranium leaves. In the time gradient, the content of citric acid (Cit) was on an upward trend, after treatment 48 h, its relative signal integral reached 4.54-fold of the unprocessed geranium leaves (control, CK). The signal integration of 13C-carbohydrate[U-13C] glucose (Gluc) and [U-13C] fructose (Fruc) decreased in the first 4 h treatment and then increased, and finally achieved 1.72 and 1.94-fold of CK. In the concentration gradient, the content of citric acid increased obviously with the increase of HCHO concentration, and finally reached 7.58-fold of CK. The signal integration of 13C-carbohydrate [U-13C] Gluc and [U-13C] Fruc slightly increased after decreased dramatically with the increase of HCHO concentration, and finally achieved 0.15 and 0.2-fold of CK. Results suggested that the HCHO-absorption by geranium leaves was a power function in relation with the treatment time. In 2 mmol/L HCHO treatment, during the early stage (0-24 h), the primary functioned metabolic pathway was the Cit produced pathway in geranium leaves. In this period, the geranium leaves absorbed 25% HCHO of total absorption. At the late stage (24-48 h) of HCHO treatment, two major metabolic pathways, the Cit produced pathway and 13C-labelled glucide ([U-13C] Gluc and [U-13C]Fruc) generation pathway, functioned simultaneously in geranium leaves. Some 13C-labelled glucide might also enter the glycolysis pathway or the tricarboxylate (TCA) cycle, which thereby allowed an enhancement in many organic acid peaks. In this time, the geranium leaves absorbed 50% HCHO of all uptake.It is concluded that HCHO is eventually converted into glyoxylate which enters into the glyoxylate cycle to produce[3-13C] Cit, and carbohydrates are synthesized via gluconeogenesis pathway, then isocitrate enters into the TCA cycle to produce amino acids, and these metabolic pathways produce various organic acids. Apparently, geranium leaves metabolize liquid formaldehyde mainly through Cit and glucide ([U-13C] Gluc and [U-13C] Fruc) synthesis pathway.